Biomechanical, physiological and anthropometrical predictors of performance in recreational runners - Peyré-Tartaruga, Leonardo A.; Machado, Esthevan; Guimarães, Patrick; Borba, Edilson; Tartaruga, Marcus P.; Buzzachera, Cosme F.; Correale, Luca; Lanferdini, Fábio Juner; da Silva, Edson Soares (PeerJ, 2024)
Background The maximal running speed (VMAX) determined on a graded treadmill test is well-recognized as a running performance predictor. However, few studies have assessed the variables that predict VMAX in recreationally active runners. Methods We used a mathematical procedure combining Fick’s law and metabolic cost analysis to verify the relation between (1) VMAX versus anthropometric and physiological determinants of running performance and, (2) theoretical metabolic cost versus running biomechanical parameters. Linear multiple regression and bivariate correlation were applied. We aimed to verify the biomechanical, physiological, and anthropometrical determinants of VMAX in recreationally active runners. Fifteen recreationally active runners participated in this observational study. A Conconi and a stead-steady running test were applied using a heart rate monitor and a simple video camera to register the physiological and mechanical variables, respectively. Results Statistical analysis revealed that the speed at the second ventilatory threshold, theoretical metabolic cost, and fat-mass percentage confidently estimated the individual running performance as follows: VMAX = 58.632 + (−0.183 * fat percentage) + (−0.507 * heart rate percentage at second ventilatory threshold) + (7.959 * theoretical metabolic cost) (R2 = 0.62, p = 0.011, RMSE = 1.50 km.h−1). Likewise, the theoretical metabolic cost was significantly explained (R2 = 0.91, p = 0.004, RMSE = 0.013 a.u.) by the running spatiotemporal and elastic-related parameters (contact and aerial times, stride length and frequency, and vertical oscillation) as follows: theoretical metabolic cost = 10.421 + (4.282 * contact time) + (−3.795 * aerial time) + (−2.422 * stride length) + (−1.711 * stride frequency) + (0.107 * vertical oscillation). Conclusion Critical determinants of elastic mechanism, such as maximal vertical force and vertical and leg stiffness were unrelated to the metabolic economy. VMAX, a valuable marker of running performance, and its physiological and biomechanical determinants can be effectively evaluated using a heart rate monitor, treadmill, and a digital camera, which can be used in the design of training programs to recreationally active runners.
Keywords: Locomotion; Maximal running speed; Maximal incremental test; Fat percentage; Anaerobic threshold; Metabolic cost; Kinematics; Heart rate